Pelaksanaan Program Pertukaran Pelajar SD Nasima ke Luar Negeri Menuju SD yang Go Internasional - Lailiya Nur Rohmah; Inarotul Latihah; Rika Aulia; Silma Maulin Najwa; Rekanita Diah Ayu Kinesti (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Educational innovation in Indonesia continues to develop to create a learning system that is adaptive to changing times. One of the efforts made is to implement the four pillars of UNESCO education, namely learning to know, learning to do, learning to be, and learning to live together. The study looked at SD Nasima Semarang, which implemented a student exchange program to support its vision of becoming an international school. Through observation and interviews, this study evaluates how daily, weekly, and flagship programs at SD Nasima, including the dual curriculum (Independent and Cambridge Curriculum), as well as extracurricular activities and habituation of manners, contribute to character formation and improvement of student competence. The findings show that the combination of these programs has succeeded in improving the quality of education, building character, and strengthening